2015
DOI: 10.1016/j.bmc.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Rat hormone sensitive lipase inhibition by cyclipostins and their analogs

Abstract: Cyclipostins are bicyclic lipophilic phosphate natural products. We report here that synthesized individual diastereomers of cyclipostins P and R have nanomolar IC50s toward hormone sensitive lipase (HSL). The less potent diastereomers of these compounds have 10-fold weaker IC50s. The monocyclic phosphate analog of cyclipostin P is nearly as potent as the bicyclic natural product. Bicyclic phosphonate analogs of both cyclipostins exhibit IC50s similar to those of the weaker diastereomer phosphates (about 400 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…In this context, we have demonstrated that the CyC analogs represent powerful and selective inhibitors of mycobacterial enzymes [14,15], with no effect on the mammalian enzymes initially targeted by natural parent molecules [14][15][16][17]. The selectivity of the CyC derivatives toward the mycobacterial but not the human enzymes, is therefore highly valuable and prompted us to consider them as potential anti-tubercular agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we have demonstrated that the CyC analogs represent powerful and selective inhibitors of mycobacterial enzymes [14,15], with no effect on the mammalian enzymes initially targeted by natural parent molecules [14][15][16][17]. The selectivity of the CyC derivatives toward the mycobacterial but not the human enzymes, is therefore highly valuable and prompted us to consider them as potential anti-tubercular agents.…”
Section: Discussionmentioning
confidence: 99%
“…New antibiotics targeting one or more proteins involved in the synthesis of mycobacterial lipids would thus represent a promising way to fight and control TB [9,13]. In this context, monocyclic enolphosphate and phosphonate analogs (CyC) of natural Cyclipostins and Cyclophostin [14][15][16][17] represent a new family of potent and selective inhibitors against mycobacteria only [18]. These CyC analogs act as powerful antitubercular agents affecting growth of M. tuberculosis both in vitro and in infected macrophages with very low toxicity towards mammalian host cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…CyC7, CyC8 and CyC17 were synthesized as previously described (31,50). To study the inhibitory effect on DGAT activity, 30 M of either Ag85A, Ag85B, Ag85C or MPT51 were coincubated with increasing concentrations of CyC7, CyC8 and CyC17 for 1 hr at room temperature in a reaction mixture containing 50 mM potassium phosphate buffer (pH 7.6), 10% DMSO and 0.5 × the critical micelle concentration (CMC) of nDodecyl β-D-maltoside (DDM).…”
Section: Methodsmentioning
confidence: 99%
“…We incremented the already available library comprising 26 CyC compounds (i.e., CyC1-18 including the cis-() and trans-() isomers), 7,10 by synthesizing 12 additional analogs (CyC19-30) from various 3-keto esters following previously described synthetic routes (Scheme 1). [3][4][5][6] The general approach previously used for the synthesis of phosphonate analogs CyC4-10 was applied (Scheme 1A) to the synthesis of cyclic phosphonates with variation in the enol alkyl substituent (CyC19-22). The palladium-catalyzed substitution reaction of methyl or ethyl acetoacetate derivatives (2) 35 with the allylic carbonate (1) gave the vinyl phosphonates (3) as an E/Z mixture in good yields (35-63%).…”
Section: Synthesis Of New Cyclophostin Phosphate and Phosphonate Analmentioning
confidence: 99%
“…To explore this hypothesis, we have reported the synthesis of Cyclipostins and Cyclophostin analogs (namely the CyCs - Figure 1). [3][4][5][6] We first demonstrated that this first series of 26 CyCs (Figure 1) was able to efficiently inhibit the growth of Mycobacterium tuberculosis H37Rv, in vitro as well as in infected macrophages, with very low toxicity towards the host cells. 7 These studies also strongly support the assumption that CyC compounds are multi-target inhibitors impairing various mycobacterial Ser-or Cys-containing enzymes involved in important physiological processes via the formation of a covalent bond between the enol-phosphorous atom and the catalytic residue.…”
mentioning
confidence: 93%